Validation of Pressure Transmitter Input/Output Loop Testing Based on Hybrid Analog and Digital HART Communication - Wintio, Rafii Trimetta; Dionova, Brainvendra Widi; Yusuf, Ahmad (Politeknik Negeri Semarang, 2025)
The use of the 4–20 mA analog signal remains a foundational standard in industrial measurement and control systems, despite the continuous advancement of digital communication technologies. This study implements a hybrid validation approach that integrates the conventional 4–20 mA analog signal with HART (Highway Addressable Remote Transducer) digital communication for conducting Input/Output (I/O) loop testing on pressure transmitters. The primary objective is to ensure the accuracy and reliability of signal transmission from field instruments to control systems such as Programmable Logic Controllers (PLCs) or Flow Computers. Utilizing a HART modem and FieldMate software, analog signals are injected and digitally monitored to verify transmitter output against predefined tolerance standards. Test results indicate that all evaluated transmitters maintained an error level below the 0.25% threshold, in compliance with standards set by the Directorate of Metrology and ASTM/API guidelines. The integration of HART communication significantly enhances testing efficiency, diagnostic capability, and remote configuration flexibility, underscoring the critical role of hybrid validation approaches in modern industrial instrumentation systems